(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study examined Rousseau’s Social Contract (RSC) with the view to determining its applicability in resolving the conflict between the Federal Government of Nigeria (FGN) and Academic Staff Union of Universities (ASUU). The study adopted a descriptive survey design in which five research questions were formulated. The population of the study consists of 3,921 subjects (13 directors of federal ministry of education and 3,908 academic staff of federal universities in South-East Nigeria. A multi-stage sampling technique was used in sampling 580 respondents (13 directors of federal ministry of education and 567 academic staff). A researcher developed questionnaire titled “Application of Rousseau’s Social Contract in conflict resolution Questionnaire (ARSCCRQ) was used for data collection. Crombach Alpha was used to ascertain the internal consistency of the instrument. This yielded reliability indices of cluster A, 0.84, Cluster B, 0.78, Cluster C, 0.88, Cluster D, 0.86 and Cluster E, 0.82 with an overall reliability score of 0.83. The five research questions were answered using mean (x) and Standard Deviation (SD). An overview of the overall results showed that academic staff unions of the university were confronted with lots of challenges in Nigerian universities. The consequences of conflicts between the FGN and ASUU in Nigerian Universities among others include: disruption of academic calendar in the Universities and closing down of universities. The issue of university funding as proposed by ASUU can be resolved by adopting the tenets of Rousseau’s general will contract. The issue of university autonomy as proposed by ASUU can be resolved through the tenets of Rousseau’s direct democracy contract and that the issue of staff conditions of service as proposed by ASUU can be resolved by adopting the tenets of Rousseau’s self enslavement contract. Considering the results of the study, the researcher among others recommends that: avenues such as seminars and workshops should be provided for the government and the university administrators to deliberate on issues regarding the university funding, university autonomy and staff conditions of service. This is necessary to ensure that the academics will neither develop attitudes of hostility towards the government nor the government becomes intolerant of the academic staff.